1999
DOI: 10.1021/js980011e
|View full text |Cite
|
Sign up to set email alerts
|

Activity–stability considerations of trypsinogen during spray drying: Effects of sucrose

Abstract: The preparation and processing of protein pharmaceuticals into powders may impose significant stresses that could perturb and ultimately denature them. In many cases their stabilization through added excipients is necessary to yield native and active proteins. In this study, the effect of spray drying on the structure and activity of a model protein (trypsinogen) was investigated. In the absence of excipients, spray drying resulted in small losses of its enzymatic activity. Protein conformational rearrangement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 39 publications
(49 reference statements)
4
60
0
Order By: Relevance
“…In addition, Schüle et al (2007) found that mannitol at relatively low concentration protected antibodies during spraydrying with inlet and outlet temperatures of 90°C and 50°C, which was similar to our spray-drying procedure. Similar results were demonstrated by Tzannis and Prestrelski (1999) and Liao et al (2002) using different sugars as the protein protectant. The protective mechanism during freeze-or spray-drying of protein models in those studies is taken place through water replacement via H-bond (Maury et al, 2005); hence preservation of protein folding occurs (Garzon-Rodriguez et al, 2004).…”
Section: Cell Envelopes and Secondary Protein Structures Of Microencasupporting
confidence: 88%
“…In addition, Schüle et al (2007) found that mannitol at relatively low concentration protected antibodies during spraydrying with inlet and outlet temperatures of 90°C and 50°C, which was similar to our spray-drying procedure. Similar results were demonstrated by Tzannis and Prestrelski (1999) and Liao et al (2002) using different sugars as the protein protectant. The protective mechanism during freeze-or spray-drying of protein models in those studies is taken place through water replacement via H-bond (Maury et al, 2005); hence preservation of protein folding occurs (Garzon-Rodriguez et al, 2004).…”
Section: Cell Envelopes and Secondary Protein Structures Of Microencasupporting
confidence: 88%
“…6,9,10 However, the mechanisms of stabilization in solid state are still not completely understood. Therefore, formulation development in the pharmaceutical industry remains an empirical effort to some extent.…”
Section: Introductionmentioning
confidence: 99%
“…Above the weight ratio of 1:1, r decreases with increasing sucrose suggesting phase separation in the formulation matrix. 9 That is, the conformation become less native above the weight ratio of 1:1 due to the phase separation.…”
mentioning
confidence: 99%
“…During spray drying, the protein is subjected to nebulization followed by air-drying; thus excipients are chosen to minimize damage due to exposure of air-water interfaces and high temperature [Tzannis and Prestrelski 1999]. Particle morphology and protein stability as a function of spray drying parameters such as input flow rates and temperature have been described [Maa et al, 1997].…”
Section: Choice Of Dosage Formsmentioning
confidence: 99%